THE INFLUENCE Of CASHLESS PAYMENT USAGE AND PROTECTION AGAINST FINANCIAL INCLUSION IN MICRO AND SMALL ENTERPRISES IN KEDIRI - Merlin Lenniawati; Njo Anastasia (International Journal of Financial and Investment Studies (IJFIS), 2020)
This study examines the effect of the use of cashless payment system and the protection of cashless payment users on financial inclusion in MSEs in Kediri. The sample used in this study amounted to 400 respondents. Data were collected using an online questionnaire via Google Form. The data analysis method used in this study is PLS. The analysis test results show that there is a significant effect of using the cashless payment system on financial inclusion in MSEs (Micro and Small Enterprises) Kediri.